2009
DOI: 10.1111/j.1749-124x.2009.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Life‐insurance Efficiency in China: A Comparison of Foreign and Domestic Firms

Abstract: The Chinese life-insurance industry has experienced major structural changes in recent years, primarily because of increasing demand and the entry of foreign insurers. Although the market is clearly booming, the efficiency of its growth and development is unclear. In this paper, we evaluate the efficiency of life insurers operating in China and compare foreign firms with domestic firms. We find that foreign insurers have not brought efficiency into the Chinese market, and that the market is still dominated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
(14 reference statements)
2
9
0
Order By: Relevance
“…This agrees with the finding of Leverty, Lin & Zhou [9] and Chen, Powers & Qiu [10], where domestic insurance had a higher level of efficiency than foreign insurance but was insignificant. This difference in yield was due to the difference in market conditions, where in China the new foreign insurance had entered the market in the 2000s, so, domestic insurance was still more dominant than foreign insurance.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This agrees with the finding of Leverty, Lin & Zhou [9] and Chen, Powers & Qiu [10], where domestic insurance had a higher level of efficiency than foreign insurance but was insignificant. This difference in yield was due to the difference in market conditions, where in China the new foreign insurance had entered the market in the 2000s, so, domestic insurance was still more dominant than foreign insurance.…”
Section: Resultssupporting
confidence: 91%
“…In addition, in Indonesia, insurance companies are divided into two ownerships, foreign and local [40]. The efficiency levels of foreign and local companies differ due to different levels of competition after the entry of foreign companies [9,10]. This research was to find the difference of efficiency performance of local and foreign insurance companies.…”
Section: A Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…4 1 While annual volumes begin in 1998, some information is available for the period 1981-1997. (Hu et al, 2009;Kweh et al, 2014), total factor productivity (Sun, 2020), economies of scale (Lu, 2019), and efficiency comparisons between domestic and foreign life insurers (Chen et al, 2009). A few life studies utilize data from other sources, most notably Swiss Re's Sigma Publications (e.g., Hwang & Gao, 2003;Hwang & Greenford, 2005).…”
Section: Data and Research Opportunitiesmentioning
confidence: 99%
“…The authors argued that domestic insurance firms are efficient than foreign insurers due to dominance by the former. However, both the categories have experienced decreasing returns to scale (Chen et al, 2009). Bawa and Navjeet (2014) have taken 4 Indian public general insurers for 21 years consisting of pre-and post-reform period and found that these insurers were comparatively better in the pre-reform period as the percentage of wastages of resources was less in this period.…”
Section: Literature Reviewmentioning
confidence: 99%